Analisis Determinan Foreign Direct Investment (FDI): Studi Kasus (Indonesia, Malaysia, Singapura, Filipina, Thailand dan Vietnam) Tahun 1997-2022 - Mu`adzah, Nayla; Sukarniati, Lestari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to analyze the influence of economic growth, corruption perception index, trade openness, market size, and financial development on foreign direct investment (FDI) in six ASEAN countries. Using the Seemingly Unrelated Regression (SUR) method and secondary data from the World Bank and Transparency International, this research combines cross section and time series data to provide a comprehensive view. The results of this research show that the corruption perception index and trade openness variables have a significant positive influence on foreign direct investment to ASEAN countries. The financial development variable has a negative and significant effect on foreign direct investment to ASEAN countries. These findings emphasize the importance of these factors in determining the direction and volume of foreign investment. This research provides an important contribution to understanding the dynamics of foreign investment in the ASEAN region and highlights the importance of efforts to increase the corruption perception index and trade openness to spur economic growth through foreign investment flows. The implications of these findings can be a policy basis for governments and stakeholders in ASEAN in increasing the attractiveness of foreign investment.